2021
DOI: 10.1039/d0ma00955e
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of nano-scale molybdenum sulfide within a metal–organic framework for highly efficient hydrodesulfurization

Abstract: AIM-X catalysts were successfully obtained by depositing MoS2 within NU-1000 through ALD. The conversion rate of the obtained AIM-60 is much better than that of the traditional MoS2/γ-Al2O3, and it can directly convert dibenzothiophene to biphenyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…[291,292] Yu et al developed an approach to synthesize a hydrodesulfurization catalyst by loading MoS 2 in NU-1000 using ALD at extraordinary desulfurization activity and high stability. [293] Catalytic oxidative desulfurization of NU-1000 was also assessed by Zheng and coworkers in the presence of H 2 O 2 which revealed excellent efficiency and good stability. [51,294]…”
Section: Desulfurizationmentioning
confidence: 99%
“…[291,292] Yu et al developed an approach to synthesize a hydrodesulfurization catalyst by loading MoS 2 in NU-1000 using ALD at extraordinary desulfurization activity and high stability. [293] Catalytic oxidative desulfurization of NU-1000 was also assessed by Zheng and coworkers in the presence of H 2 O 2 which revealed excellent efficiency and good stability. [51,294]…”
Section: Desulfurizationmentioning
confidence: 99%
“…In an early study published in 2015, Hupp, Farha and co-workers have reported the use of atomic layer deposition (ALD) to deposit the spatially separated clusters of cobalt sulphide into a Zr-MOF, with the use of H 2 S vapor as the precursor; 35 similar approaches were also used to synthesize the few-atom clusters of metal sulphides installed in Zr-MOFs. [36][37][38] Compared to the few-atom clusters immobilized on the nodes of Zr-MOFs, we reasoned that the nanoparticles of metal sulphide that are physically confined within the MOF pore should possess more similar properties to the bulk metal sulphide, and the particle size could be highly tuneable by simply adjusting the pore size of the selected MOF. The rigid framework of Zr-MOF is expected to effectively prevent further agglomeration of nanoparticles, which should result in a high external surface area of the metal sulphide that is beneficial for heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the study of different supports, the development of solid metal-organic framework (MOF) has grown considerably by bringing together a variety of textural properties such as high porosity, large surface areas, low structure density and the viability to modulate its structure with specific active centers for applications in catalytic and photocatalytic functions [33][34][35][36][37]. In this continuous development, different molybdenum active centers have been successfully incorporated into metal-organic structures with diversity of applications such as aerobic alcohols oxidations [38], hydrocarbons hydrodesulfurization processes [39,40] and epoxidation of alkenes and cycloalkenes [41,42] among others, leading to progress and approaches in the insights into the structure-activity relationship.…”
Section: Introductionmentioning
confidence: 99%